Prospective Associations of Insomnia Markers and Symptoms With Depression - Szklo-Coxe, Mariana (Oxford University Press, 2010)
Whether insomnia, a known correlate of depression, predicts depression longitudinally warrants elucidation. The authors examined 555 Wisconsin Sleep Cohort Study participants aged 33–71 years without baseline depression or antidepressant use who completed baseline and follow-up overnight polysomnography and had complete questionnaire-based data on insomnia and depression for 1998–2006. Using Poisson regression, they estimated relative risks for depression (Zung scale score ≥50) at 4-year (average) follow-up according to baseline insomnia symptoms and polysomnographic markers. Twenty-six participants (4.7%) developed depression by follow-up. Having 3–4 insomnia symptoms versus none predicted depression risk (age-, sex-, and comorbidity-adjusted relative risk (RR) = 3.2, 95% confidence interval: 1.1, 9.6). After multiple adjustments, frequent difficulty falling asleep (RR = 5.3, 95% confidence interval: 1.1, 27.9) and polysomnographically assessed (upper or lower quartiles) sleep latency, continuity, and duration (RRs = 2.2–4.7; P’s ≤ 0.05) predicted depression. Graded trends (P-trend ≤ 0.05) were observed with increasing number of symptoms, difficulty falling asleep, and difficulty returning to sleep. Given the small number of events using Zung ≥50 (depression cutpoint), a limitation that may bias multivariable estimates, continuous depression scores were analyzed; mean values were largely consistent with dichotomous findings. Insomnia symptoms or markers increased depression risk 2.2- to 5.3-fold. These results support prior findings based on self-reported insomnia and may extend similar conclusions to objective markers. Heightened recognition and treatment of insomnia may prevent subsequent depression.